COMPARATIVE EVALUATION OF THE FREQUENCY OF RISK FACTORS FOR THE DEVELOPMENT OF CORONARY HEART DISEASE AND ARTERIAL HYPERTENSION IN MINERS WITH ANTHRACOSILICOSIS - Панев, Николай Иванович; Евсеева, Наталья Александровна (Medicine in Kuzbass, 2022)
The aim of the research was to study the frequency and identify the most significant cardiovascular risk factors in patients with anthracosilicosis in combination with arterial hypertension and coronary heart disease.Materials and methods. The study involved 269 workers of the main professions of coal mines (drifters, stope miners, mining machine operators): 139 miners with a previously proven diagnosis of anthracosilicosis, 130 miners of the control group (workers with long-term labor experience without lung pathology and occupational diseases). All surveyed subjects were men aged 40 to 54 years. All participants underwent a comprehensive clinical, laboratory and instrumental examination to identify occupational pulmonary pathology, cardiovascular diseases and cardiovascular risk factors. Statistical data processing was carried out using the EXCEL and STATISTICA software packages.Results. In miners with anthracosilicosis, arterial hypertension and coronary artery disease were more common than in workers with long-term labor experience. The most significant cardiovascular risk factors in patients with anthracosilicosis in combination with arterial hypertension were revealed: smoking (especially with a smoking index above 20), abdominal obesity type, personality type A, excessive salt intake, fasting hyperglycemia, hyperhomocysteinemia, hyperuricemia. The most significant cardiovascular risk factors in patients with anthracosilicosis in combination with coronary artery disease were identified: smoking, abdominal obesity type, arterial hypertension, metabolic syndrome, decreased levels of high-density lipoproteins, increased levels of C-reactive protein and homocysteine, increased fibrinogen levels and soluble fibrin-monomer complexes.Conclusions. A high prevalence of traditional cardiovascular risk factors in patients with anthracosilicosis was noted. The most significant factors of cardiovascular risk in patients with anthracosilicosis in combination with arterial hypertension and coronary artery disease have been identified. Timely detection and elimination of cardiovascular risk factors is an effective way to prevent vascular morbidity in workers in hazardous labor conditions.
Keywords: miners; anthracosilicosis; cardiovascular risk factors